S112 Estimating Participation Rates of COPD Patients in Pulmonary Rehabilitation and Self-Management Programmes: The Importance of Defining Participation. (19th November 2012) - Sohanpal, R; Hooper, RL; Hames, R; Priebe, S; Taylor, SJC
Abstract : Introduction and Objectives: Delivery of pulmonary rehabilitation (PR) and self-management (SM) support programmes to patients living with chronic obstructive pulmonary disease (COPD) is emphasised in national guidelines, but these interventions are not always routinely available. One potential explanation for the lack of implementation could be the poor patient participation and retention reported in the literature. We conducted a systematic review to determine a true estimate of participation and dropout rates. Methods: Studies were identified from eight electronic databases including MEDLINE. Controlled clinical trials of structured SM, PR and health education (HE) programmes for COPD were included. Data extraction included 'participant flow' data using the Consolidated Standards of Reporting Trials (CONSORT) statement and its extension to pragmatic trials. Patient 'participation rates' (study participation rate (SPR), study dropout rate (SDR) and intervention dropout rate (IDR)) were calculated using prior definitions consistent with CONSORT Random effects logistic regression analysis was conducted to examine effects of four key study characteristics on participation rates. Results: 56 quantitative studies (51 randomised controlled trials, three quasi-experimental and two before-after studies) evaluated PR (n=31), SM (n=21) and HE (n=4). Reports of participant flow were generally incomplete; 'numbers of potential participants identified' were only available for 16%, and 'numbers assessed for eligibility' for only 39% of studies. Although 'numbers eligible' were better reported (77%), we were unable to calculate SPR for 23% of studies. Overall we found 'participation rates' for studies (n=43) were higher than previous reports; only 19% of studies had less than 50% SPR and just over one third (34%) had a SPR of 100%; SDR and IDR were less than or equal to 30% for around 93% of studies. There was no evidence of effect of study characteristics on participation rates. Conclusion: Unlike previous reports, we found high participation and low dropout rates in studies of PR or SM support for COPD Previous studies adopted different participation definitions; some reported proportions without stating definitions clearly, obscuring whether proportions referred to the study or the intervention. Clear, uniform definitions of patient participation in studies are needed to better inform the wider implementation of effective interventions.